Monocyte-derived dendritic cells can be detected in urine of kidney transplant recipients with pathogenic asymptomatic bacteriuria - Salvadé, Vanja; Manuel, Oriol; Golshayan, Dela; Obregon, Carolina (Frontiers in Transplantation, 2024)
Urinary tract infections (UTI) are an important clinical problem in kidney transplant recipients (KTR). Asymptomatic bacteriuria (ASB) is frequent in these patients and often resolved by the immune system, but a significant proportion may progress to complicated UTI, which may compromise allograft function and survival. It is essential to determine the involvement of the immune system in the infectious process. Dendritic cells (DCs) are recognised as playing a pivotal role in initiating inflammatory responses capable of priming antigen-specific T cells, a crucial step in determining the fate of local inflammation. Little is known about their role in the control of UTI. In this brief communication, we report an incidental finding in a group of 16 stable KTR in which monocyte-derived dendritic cells (ModDCs), analysed by flow cytometry, were found in urine of patients with ASB and high bacterial counts >10 7 cfu/mL. Within this group, one patient developed pyelonephritis in the following days. These findings suggest that the immune system, in particular DCs, may be recruited during the course of a UTI and, to our knowledge, present for the first time evidence that inflammatory ModDCs can be detected in urine. Their frequency may reflect the degree of infection. This finding suggests the potential for exploring whether these cells may be useful in distinguishing between pathogenic ASB and those that can be resolved by the immune system.